2016
DOI: 10.1189/jlb.3ri0516-222r
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota—myeloid cell crosstalk beyond the gut

Abstract: The gut microbiota is a complex and dynamic microbial ecosystem that plays a fundamental role in host physiology. Locally, the gut commensal microbes/host symbiotic relationship is vital for barrier fortification, nutrient absorption, resistance against intestinal pathogens, and the development and maintenance of the mucosal immune system. It is now clear that the effects of the indigenous intestinal flora extend beyond the gut, ranging from shaping systemic immune responses to metabolic and behavioral functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 131 publications
1
56
0
Order By: Relevance
“…Many myeloid cells in the intestine, such as macrophages and dendritic cells, are activated by the intestinal flora to initiate innate and adaptive immunity, and inflammatory reactions (43). In addition, intestinal epithelial cells, as the first barrier of innate regional immunity, play an important role in activating the immune system and protecting the host from pathogens (44).…”
Section: Intestinal Flora Activates the Intestinal Immune Systemmentioning
confidence: 99%
“…Many myeloid cells in the intestine, such as macrophages and dendritic cells, are activated by the intestinal flora to initiate innate and adaptive immunity, and inflammatory reactions (43). In addition, intestinal epithelial cells, as the first barrier of innate regional immunity, play an important role in activating the immune system and protecting the host from pathogens (44).…”
Section: Intestinal Flora Activates the Intestinal Immune Systemmentioning
confidence: 99%
“…Chronic infection of S. enterica typhi in the gastrointestinal tract has been associated with pancreatic and lung cancer . More broadly, the gut microbiota appears to have systemic effects on the immune system . Several studies have reported systemic Th17 inflammation or anti‐inflammatory Treg activation due to the presence of commensal microbes of the gut .…”
Section: The Gut Microbiome and Cancermentioning
confidence: 99%
“…SCFA binding to GPRs expressed on leucocytes, including neutrophils, eosinophils and macrophages, has been found to influence myelopoiesis and myelocyte migration . Intravascular recruitment of neutrophils induced by an LPS challenge was increased in Gpr43 −/− mice compared with wildtype mice .…”
Section: Microbiome Innate Immunity and Asthma Protectionmentioning
confidence: 97%
“…111 SCFA binding to GPRs expressed on leucocytes, including neutrophils, eosinophils and macrophages, has been found to influence myelopoiesis and myelocyte migration. [112][113][114] Intravascular recruit-…”
Section: G-protein-coupled Receptors and Short-chain Fatty Acidsmentioning
confidence: 99%